KONSEP KEPEMIMPINAN ABAD 21 DALAM PENGEMBANGAN LEMBAGA PENDIDIKAN TINGGI ISLAM - Bashori, Bashori; Yolanda, Mardivta; Wulandari, Sonia (UIN Imam Bonjol Padang, 2020)
Descriptions and thoughts about leadership in the 21st century depart from the view that leaders must correctly and completely recognize the conditions and aspirations of the community or the people they lead. The leader's responsibility is to provide solutions wisely, effectively, and productively for the various problems and challenges it faces. For that, every leader needs to meet certain competencies and qualifications. Therefore, this study aims to determine the definition of leadership, functions, and leadership goals for Islamic higher education institutions in the 21st century, as well as the challenges of 21st century leadership and the urgency of leadership for Islamic educational institutions. This research method is qualitative through a content analysis approach with data collection techniques through various relevant references. The results of this study indicate that the leaders of the 21st century, namely; 1) Leaders who like and are able to face various challenges; 2) Leaders who are curious about various things; 3) Leaders who are able to build an established, conducive and professional work culture and organization; 4) Leaders who are able to build communication with various lines; 5) Leaders who have a commitment to progress, prosperity, and excellence.